Effects of Sand–Cement Columns on Primary Consolidation Settlement - Benjamin Abankwa; Mehrdad Razavi; Richard Otoo; Abraham Armah; Sandra Donkor (Applied Sciences)
The rapid increase in population and the corresponding increase in developments have necessitated the stabilization of areas with poor soil conditions. Due to consolidation settlement, the soft grounds available are deemed unsuitable for such structures. This paper presents the use of cement additives to build sand–cement columns in saturated clayey soils. The approach significantly reduces consolidation settlement and increases the bearing capacity, providing a viable solution to foundation problems. Consolidation tests were conducted on saturated clay specimens and sand–cement columns arranged in various patterns. A 5% cement content by the dry weight of the sand was used in building sand–cement columns. The results showed that the consolidation settlement rate was high due to the extra drainage formed by the widened pores in the sand–cement columns. The extra drainage caused more water to leave the specimen in a given time. However, after full contact between the loading platen and sand–cement columns, the rate of consolidation settlement decreased. At this stage, sand–cement participated in carrying the load. Additionally, the effect of vertical drainage on speeding up consolidation at higher stress levels was minimal, as the widened pores in the sand–cement columns began to close.